Brain–computer interface boosts motor imagery practice during stroke recovery. Issue 5 (27th March 2015) - Pichiorri, Floriana; Morone, Giovanni; Petti, Manuela; Toppi, Jlenia; Pisotta, Iolanda; Molinari, Marco; Paolucci, Stefano; Inghilleri, Maurizio; Astolfi, Laura; Cincotti, Febo; Mattia, Donatella
<x xml:space="preserve">Abstract</x> Objective Motor imagery (MI) is assumed to enhance poststroke motor recovery, yet its benefits are debatable. Brain–computer interfaces (BCIs) can provide instantaneous and quantitative measure of cerebral functions modulated by MI. The efficacy of BCI‐monitored MI practice as add‐on intervention to usual rehabilitation care was evaluated in a randomized controlled pilot study in subacute stroke patients. Methods Twenty‐eight hospitalized subacute stroke patients with severe motor deficits were randomized into 2 intervention groups: 1‐month BCI‐supported MI training (BCI group, n = 14) and 1‐month MI training without BCI support (control group; n = 14). Functional and neurophysiological assessments were performed before and after the interventions, including evaluation of the upper limbs by Fugl–Meyer Assessment (FMA; primary outcome measure) and analysis of oscillatory activity and connectivity at rest, based on high‐density electroencephalographic (EEG) recordings. Results Better functional outcome was observed in the BCI group, including a significantly higher probability of achieving a clinically relevant increase in the FMA score (p < 0.03). Post‐BCI training changes in EEG sensorimotor power spectra (ie, stronger desynchronization in the alpha and beta bands) occurred with greater involvement of the ipsilesional hemisphere in response to MI of the paralyzed trained hand. Also, FMA improvements (effectiveness of FMA) correlated with the changes (ie, post‐training increase) at rest in ipsilesional intrahemispheric connectivity in the same bands (p < 0.05). Interpretation The introduction of BCI technology in assisting MI practice demonstrates the rehabilitative potential of MI, contributing to significantly better motor functional outcomes in subacute stroke patients with severe motor impairments. Ann Neurol 2015;77:851–865